The Effect of Standing Board Jump and Jump Rope Training on the Ability of Long Jump Squatting Style of Students in SD Negeri 12 Palembang - Fachma, Rizka Febrian; Rosani, Meilia; Putri, Siti Ayu Risma (Yayasan Sembilan Pemuda Indonesia, 2023)
The problem in this study is whether there is a difference in the effect between standing board jump training and jump rope training on the results of long jump squatting style in class VI students of SD Negeri 12 Palembang. This study aims to determine the difference in the effect of standing board jump training and jump rope training on the results of long jump squatting style in grade VI students of SD Negeri 12 Palembang. This type of research is experimental research, using the M-S Pattern method. The population in this study were 6th grade students of SD Negeri 12 Palembang with a total of 30 people. The sampling technique in this study used total sampling technique. The variables of this study consisted of independent variables, namely standing board jump and jump rope training, as well as the dependent variable of squatting style long jump ability. Data collection using the squatting style long jump test method. The data analysis technique uses the t-test formula. Based on the results of research that has been conducted on grade VI students of SD Negeri 12 Palembang, about the effect of standing board jump training and jumping rope on the learning outcomes of long jump squatting style as many as 30 students (sample). The results showed that t value 4.42 > t critical 2.66 at a significant level with db58 means that there is a difference in influence between Standing board jump and jump rope training on the ability of grade VI students of SD Negeri 12 Palembang. From the calculation of the mean, it shows that the mean of experimental group 1 is greater than group 2 (3.63 < 3.53). Thus, it can be concluded that jump rope training has more effect than standing board jump training.